ENGLISH TEXTBOOKS FOR YOUNG LEARNERS USED IN TWENTY-FIVE PRIMARY SCHOOLS IN BANDUNG KULON - Rahayu Utami Komalaningsih, - (2009)
This research analyzes the extent to which materials contained in English textbooks for young learners accommodate young learners' characteristics and identify kinds of supports that are provided for teachers in order to help them use the textbooks in their instructions. In this research, a mixed form between quantitative and qualitative research is employed as the research design. The data for this research are taken from a series of textbooks published by a particular publisher that is mainly used by English teachers in primary schools in Bandung Kulon. The textbooks are written for grade 4, 5, and 6 of primary schools. With reference to young learners' characteristics and criteria of good English textbooks, both in terms of textbooks for general and textbooks for young learners, the data are then examined and analyzed by using a checklist adapted from Scott and Ytreberg's theory. The findings show that the three textbooks do not sufficiently accommodate young learners' characteristic because although they are good in terms of physical appearance, they only accomplish two from ten criteria of contents in the checklist of good English textbooks for young learners. The three textbooks also do not provide adequate supports for teachers.